Aberrant activity and connectivity of the posterior superior temporal sulcus during social cognition in schizophrenia - Mier, Daniela; Meyer-Lindenberg, Andreas; Zink, Mathias; Kirsch, Peter (European archives of psychiatry and clinical neuroscience, 2017)
Schizophrenia is associated with significant impairments in social cognition. These impairments have been shown to go along with altered activation of the posterior superior temporal sulcus (pSTS). However, studies that investigate connectivity of pSTS during social cognition in schizophrenia are sparse. Twenty-two patients with schizophrenia and 22 matched healthy controls completed a social-cognitive task for functional magnetic resonance imaging that allows the investigation of affective Theory of Mind (ToM), emotion recognition and the processing of neutral facial expressions. Moreover, a resting-state measurement was taken. Patients with schizophrenia performed worse in the social-cognitive task (main effect of group). In addition, a group by social-cognitive processing interaction was revealed for activity, as well as for connectivity during the social-cognitive task, i.e., patients with schizophrenia showed hyperactivity of right pSTS during neutral face processing, but hypoactivity during emotion recognition and affective ToM. In addition, hypoconnectivity between right and left pSTS was revealed for affective ToM, but not for neutral face processing or emotion recognition. No group differences in connectivity from right to left pSTS occurred during resting state. This pattern of aberrant activity and connectivity of the right pSTS during social cognition might form the basis of false-positive perceptions of emotions and intentions and could contribute to the emergence and sustainment of delusions.